1994
DOI: 10.1016/0004-3702(94)90071-x
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of terminological representation systems

Abstract: This work may not be copied or reproduced in whole or in part for any commercial purpose. Permission to copy in whole or in part without payment of fee is granted for nonprofit educational and research purposes provided that all such whole or partial copies include the following: a notice that such copying is by permission of Deutsches Forschungszentrum fur Kunstliche Intelligenz. Kaiserslautern, Federal Republic of Germany; an acknowledgement of the authors and individual contributors to the work; all applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Studies on selected services have shown that websites providing appropriate metadata for SearchMonkey have a 15% higher click-trough-rate once the website made it to the top 10 results. 30 Other companies such as BestBuy.com even report higher traffic of about 30% since they have started publishing semantic data with their website in September 2009. describe its e-commerce offerings. Also Google has started exploiting semantic data from e-commerce websites describing their products with the GoodRelations vocabulary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on selected services have shown that websites providing appropriate metadata for SearchMonkey have a 15% higher click-trough-rate once the website made it to the top 10 results. 30 Other companies such as BestBuy.com even report higher traffic of about 30% since they have started publishing semantic data with their website in September 2009. describe its e-commerce offerings. Also Google has started exploiting semantic data from e-commerce websites describing their products with the GoodRelations vocabulary.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, description logics systems, which are now the backbone of Web Ontologies, were severely limited in scale, typically capable of handling not more than a few hundred concepts in the mid 1990's (cf. [30]). In the meanwhile, several such problems have been overcome using much increased computational power as well as better understood and optimized algorithms leading to the practical handling of large ontologies such as SNOMED 6 with several hundreds of thousands of axioms (cf.…”
Section: Architecture For Representing Knowledge On the Webmentioning
confidence: 99%
“…an arbitrary KB) is of a relatively high complexity (EXPTIME-complete), the pathological cases that lead to such high worst case complex-ity are rather artificial, and rarely occur in practice [127,86,155,95]. Even in realistic applications, however, problems can occur that are much too hard to be solved by naive implementations of theoretical algorithms such as the one sketched in Section 3.4.1.…”
Section: Implementation and Optimisation Techniquesmentioning
confidence: 99%
“…Yelland (53) for instance, proposed a scheme for integration of subsumption mechanisms smoothly integrated with object structures. The main problem with these powerful mechanisms is that they are not complete (for ex., see (27) for an evaluation of various terminological systems). In our context, we believe that the sophistication of subsumption mechanisms is not needed, since the collection of potential solutions is to support only limited extensions.…”
Section: Representing the Taxonomy Of Possible Solutions -Partmentioning
confidence: 99%